(untitled) - 1979-; Brown, Peter (New York, New York, 2023)
"Roz must take an under-the-ocean journey to save her island from a mysterious poison tide"--Provided by publisher.
Keywords: Animals; Juvenile fiction; Islands; Juvenile fiction; Voyages and travels; Juvenile fiction; Poisons; Juvenile fiction; Robots; Juvenile fiction; Sea stories; Juvenile fiction; Science fiction; Juvenile fiction